A new species of the cardinalfish genus Jaydia (Teleostei: Apogonidae) from the Philippines - Gon, Ofer; Liao, Yun-Chih; Kwang-Tsao, Shao (Zootaxa, 2015)
Jaydia erythrophthalma n. sp. is described from specimens collected during two recent biodiversity surveys along the east and west coasts of Luzon, Philippines. It is characterized by a first dorsal fin with eight spines, serrated posterior and crenulated ventral preopercular edges, reddish orange iris and two series of brown spots tinged in orange on the upper part of the body.